Does the Christian worldview provide a place for the law of attraction? (Part 1): An apologetic evaluation of the roots of this doctrine - Maritz, Daniël J.; Stoker, Henk G. (Verbum et Ecclesia, 2016)
This article investigates the roots of the so-called spiritual law of attraction that some Christian preachers today describe as an important biblical law. One of the proponents of this idea, Pastor At Boshoff of the Christian Revival Church (CRC), refers in his sermons to the law of attraction as a powerful principle derived from the Word of God. This idea bears striking similarities to the positive confession doctrine as taught by popular Word of Faith preachers. The basic claim of this spiritual ‘law’ is that human beings create their own future through their thoughts and words. The article shows the idea of a spiritual law of attraction as a New Age doctrine that flows from a New Age worldview. Preaching prosperity through the law of attraction is not in accordance with orthodox, historical Christianity or the Christian worldview. Intradisciplinary and/or interdisciplinary implications: The article challenges the secular view that intangible thoughts and words can take on tangible reality. This is important since this secular idea is infiltrating the Christian church. It is already being preached as biblical although the roots thereof are clearly shown to originate from the New Age movement.
free